Soil management and smallholder development in the Pacific Islands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Soil Management and Smallholder Development in the Pacific Islands - Pacificland, IBSRAM 1989 ISBN 974 7613 20 4